COLLABORATIVE PATTERNS OF LONG-TERM SUSTAINABILITY IN COMMUNITY SOCIAL ENTERPRISES: AN INTERNATIONAL COMPARATIVE CASE STUDY - Kovanen, Sunna (Quaestiones Geographicae, 2020)
The article presents results from a research on the relevance and challenges of collaboration for the long-term sustainability of rural community enterprises. The study relies on Communities of Practice and Degrowth theories. Methods include semi-standardised interviews and focused ethnography in two community enterprises in rural areas in Germany and Portugal. Main results confirm the relevance of collaborative relations with residents, public sector, peer organisations and within the teams for both stability and transformative power of the organisations’ work. Respectful handling of privileges and balance in participation and professionalisation support sustainability, whereas institutional stagnation and involuntary degrowth may risk it.